Severe trauma associated cardiac failure - Maximilian Dietrich; Frank Weilbacher; Stephan Katzenschlager; Markus A. Weigand; Erik Popp (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Although significant efforts have been made to enhance trauma care, the mortality rate for traumatic cardiac arrest (TCA) remains exceedingly high. Therefore, our institution has implemented special measures to optimize the treatment of major trauma patients. These measures include a prehospital Medical Intervention Car (MIC) and a ‘code red’ protocol in the trauma resuscitation room for patients with TCA or shock. These measures enable the early treatment of reversible causes of TCA and have resulted in a significant number of patients achieving adequate ROSC. However, a significant proportion of these patients still die due to circulatory failure shortly after. Our observations from patients who underwent clamshell thoracotomy or received echocardiographic evaluation in conjunction with current scientific findings led us to conclude that dysfunction of the heart itself may be the cause. Therefore, we propose discussing severe trauma-associated cardiac failure (STAC) as a new entity to facilitate scientific research and the development of specific treatment strategies, with the aim of improving the outcome of severe trauma.